Trends in summer bottom-water temperatures on the northern Gulf of Mexico continental shelf from 1985 to 2015. - R Eugene Turner; Nancy N Rabalais; Dubravko Justić (PLoS ONE)
We quantified trends in the 1985 to 2015 summer bottom-water temperature on the northern Gulf of Mexico (nGOM) continental shelf for data collected at 88 stations with depths ranging from 3 to 63 m. The analysis was supplemented with monthly data collected from 1963 to 1965 in the same area. The seasonal summer peak in average bottom-water temperature varied concurrently with air temperature, but with a 2- to 5-month lag. The summer bottom-water temperature declined gradually with depth from 30 oC at stations closest to the shore, to 20 oC at the offshore edge of the study area, and increased an average 0.051 oC y-1 between1963 and 2015. The bottom-water warming in summer for all stations was 1.9 times faster compared to the rise in local summer air temperatures, and 6.4 times faster than the concurrent increase in annual global ocean sea surface temperatures. The annual rise in average summer bottom-water temperatures on the subtropical nGOM continental shelf is comparable to the few published temperature trend estimates from colder environments. These recent changes in the heat storage on the nGOM continental shelf will affect oxygen and carbon cycling, spatial distribution of fish and shrimp, and overall species diversity.